Madlenka, soccer star - Sís, Peter, 1949- (Frances Foster Books, 2010)
Madlenka plays soccer in her city neighborhood--with the mailbox, a dog, a parking meter, and some cats. Includes a brief history of soccer and words for soccer around the world.